Susceptibility to tuberculosis: A locus on mouse chromosome 19 (Trl-4) regulates Mycobacterium tuberculosis replication in the lungs - Mitsos, Loukia-Maria (National Academy of Sciences, 2003)
The mouse DBA/2 (D2) strain is very susceptible to infection with virulent Mycobacterium tuberculosis, whereas C57BL/6 (B6) is much more resistant. Infection of D2 and B6 mice with M. tuberculosis H37Rv by the respiratory route is biphasic: during the first 3 weeks, there is rapid bacterial growth in the lung of both strains, whereas beyond this point replication stops in B6 but continues in D2, causing rapidly fatal pulmonary disease. To identify the genes regulating growth of M. tuberculosis in the lungs of these two strains, 98 informative (B6 × D2) F(2) mice were infected by the respiratory route with M. tuberculosis H37Rv (2 × 10(2) colony-forming units), and the extent of bacterial replication in the lungs at 90 days was used as a quantitative measure of susceptibility in a whole-genome scan. Quantitative trait locus mapping identified a major locus on chromosome 19 (Tuberculosis resistance locus-4, Trl-4; logarithm of odds 5.6), which regulated pulmonary replication of M. tuberculosis and accounted for 25% of the phenotypic variance. B6 alleles at Trl-4 were inherited in an incompletely dominant fashion and associated with reduced bacterial replication. An additional effect of a locus (Trl-3), previously shown to affect survival to i.v. infection with M. tuberculosis, was also noted. F(2) mice homozygous for B6 alleles at both Trl-3 and Trl-4 were as resistant as B6 parents, whereas mice homozygous for D2 alleles were as susceptible as D2 parents. These results suggest a strong genetic interaction between Trl-3 and Trl-4 in regulating pulmonary replication of M. tuberculosis.